2022
DOI: 10.1088/1361-648x/ac5706
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metal–insulator interface interactions on electrical transport in granular metals

Abstract: We present an in-depth study of metal–insulator interfaces within granular metal (GM) films and correlate their interfacial interactions with structural and electrical transport properties. Nominally 100 nm thick GM films of Co and Mo dispersed within yttria-stabilized zirconia (YSZ), with volumetric metal fractions (φ) from 0.2–0.8, were grown by radio frequency co-sputtering from individual metal and YSZ targets. Scanning transmission electron microscopy and DC transport measurements find that the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…The percolation threshold (j c ) is the metal fraction where the GM's electronic nature switches from insulating to metallic, and occurs in the j = 0.3-0.6 range. Below j c , the room temperature DC conduction is dominated by thermally-assisted electron tunneling, which depends on the prevalence of insulator defects and the separation distance between metal nanoparticles [4,5]. The capacitive transport dominates at high frequencies and scales according to Jonscher's universal power law [6,7] as confirmed by experiments [8,9].…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…The percolation threshold (j c ) is the metal fraction where the GM's electronic nature switches from insulating to metallic, and occurs in the j = 0.3-0.6 range. Below j c , the room temperature DC conduction is dominated by thermally-assisted electron tunneling, which depends on the prevalence of insulator defects and the separation distance between metal nanoparticles [4,5]. The capacitive transport dominates at high frequencies and scales according to Jonscher's universal power law [6,7] as confirmed by experiments [8,9].…”
Section: Introductionmentioning
confidence: 76%
“…While GMs with various metals have been investigated, nearly all GM studies employed oxide-based insulators, such as SiO 2 , Al 2 O 3 , or yttria-stabilized zirconia (YSZ), with notable non-oxides including MgF 2 [18], BN [19], and carbon-based [20,21] GMs. Recently, we found that GMs with non-noble metals and oxide insulators form metal-oxides, which deleteriously increase GM conductivity at j < j c [5]. Annealing of GMs causes nanoparticle coalescence and substantially alters the GM electrical properties [2]; high thermal stability transition metal-based GMs will enable applications at elevated temperatures and high current densities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations